Review of 1971/06/25 and 1971/06/26 Concerts at Arts Laboratory Newton, Birmingham. "The Super Spectacular Symmetry Show" presented by Birmingham Arts Laboratory Sound Workshop with Embarkation - Gatiss, J. Christopher (Contact: A Journal for Contemporary Music (1971-1990), 1971)